War and the environment : military destruction in the modern age - Closmann, Charles E. (Charles Edwin), 1957- (Williams-Ford Texas A&M University military history series ;, 2009)
"In recent times, the devastation occurring in places like Darfur has focused the world's attention on the intertwined relationship of military conflict and the environment -- and the attendant human suffering. In War and the Environment, eleven scholars explore, among other topics, the environmental ravages of trench warfare in World War I, the exploitation of Philippine forests for military purposes from the Spanish colonial period through 1945, William Tecumseh Sherman's scorched-earth tactics during his 1864-65 March to the Sea, and the effects of wartime policy upon U.S. and German conservation practices during World War II"--Publisher's description.